COVID-19 disruption in agricultural input supply and impact on food security in Nepal - Gautam, Shriniwas; Dongol, Prabin; Khanal, Narayan P.; Issa, Abdurahman Beshir; Choudhary, Dyutiman (University of the West Indies, 2023)
This study assesses the extent of COVID-19 pandemic disruptions in Nepal on the availability and access of agricultural inputs and the impact on agricultural production and food security using data from a key informant survey conducted in 2020. The pandemic disruptions in the business sector (retail and wholesale) were more severe than in the agriculture sector, even though agriculture was reported as the most critical for the livelihood of most of the surveyed communities. Due to a scarcity of imported agricultural inputs like seeds, fertilizers, and pesticides, the use of locally available seeds increased, resulting in a marginal reduction in the cultivation of maize and rice in 2020 (during COVID-19) compared to 2019 (before COVID-19). The key informants expected a significant reduction in rice and maize production and an increase in the percentage of food-insecure households in their communities in 2020 compared to 2019. The disruptions caused by COVID-19 underscore the need for reflection, revealing the unpreparedness of both governmental and private sectors in provisioning and distributing agricultural inputs. Some recommendations we provide could help lessen the adverse effects of potential future disruptions in agricultural input value chains.